The Dutch bulk carrying traffic to Elbing in the seventeenth century (1585-1700). The narrowing of the 'Mother trade' - Israel, J. (BMGN - Low Countries Historical Review, 1997)
J.Th. Lindblad, F.C. Dufour-Briët, Dutch entries in the Pound-toll registers of Elbing 1585-1700